Analisis Yuridis Tindak Pidana Korupsi Yang Dilakukan Oleh Aparatur Sipil Negara Ditinjau Dalam Undang-Undang Nomor 5 Tahun 2014 Tentang Aparatur Sipil Negara - Indra Kumalasari M. (Universitas Islam Sumatera Utara, 2018)
Corruption is stipulated in Law No. 20, 2001 concerning to Amendment to Law No. 31,1999 about the Eradication of Corruption which is regulated in Article 2 (1). Everyone who unlawfully enforces the act of enriching himself or a corporation that can harm the state’s finances or the economy, will be sentenced to a life imprisonment or imprisonment of 4 (four) years minimally and 20 (twenty) years maximally and a fine of at least 200.000.000 Rupiahs (two hundred million rupiahs) and at most 1.000.000.000 Rupiahs (one billion rupiahs). The Civil State Apparatus Act is a law to regulate the profession for civil servants and government employees with employment agreements in governmental agencies. Dismissal as a Civil Servant results in the loss of a Civil Servant status. Disrespectful dismissal of a Civil Servant is due to corruption which is detrimental to the state's finances. Law No. 20, 2001 contains the criminal and civil sanctions to the State Civil Apparatus who commit corruption. Keywords: Corruption, State Civil Apparatus